Development, processing, and acceptance of a faba bean (Vicia faba) based porridge - Perez, Jazmín Osorio (2022)
The development of legume-based food products allows the promotion of healthy and nutritious plant-based alternatives, which are also environmentally sustainable. Porridges are often healthy, simple to prepare and suitable for various segments of the population, constituting a good option for food innovation. In this study a faba bean-based porridge was developed, using freeze-dried faba bean flour. A randomised sensorial analysis was performed. In terms of colour, 43% of panellists indicated that they “like it to some extent”, while the texture was the most appreciated characteristic which was evaluated. Results showed that overall appreciation of the porridge was 40%.